Comparative analysis of four biomarkers in diagnosing premature rupture of membranes and their correlation with onset of labour - Tigga, Maureen Prativa; Malik, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The diagnosis of equivocal cases of premature rupture of membranes (PROM) with traditional methods has been unreliable therefore various biochemical markers have been sought to confirm the same. This study aims to determine the most reliable marker amongst β human chorionic gonadotropin (βhCG) ά fetoprotein (AFP), prolactin and creatinine in vaginal washing for diagnosing PROM and to establish the correlation between the level of these markers and the onset of labour. Methods: Fifty pregnant women between 20 and 40 weeks of gestation with history of leaking per vaginum (study group) and an equal number of gestation matched pregnant women without leak (control group) were recruited to the study. All women underwent speculum examination aiming to sample and assay the two markers. The duration from PROM to onset of labour was recorded in the study group. Data was analyzed by student’s t-test, receiver operator curve and chi square test. Results: Vaginal washing concentration of the markers were significantly higher in the study group (p<0.01) thereby rendering them as markers for diagnosing PROM. There was negative correlation coefficient between the levels of markers and duration from PROM to onset labour, denoting early onset of labour in patients with higher levels of markers. Conclusions: AFP and creatinine were better markers for diagnosing premature rupture of membranes while β human chorionic gonadotropin was the better predictor of onset of labour.